What is the student response to using the weblogs for learning resources?. Issue 3 (February 2019) - Astuti, I A D; Sulisworo, D; Firdaus, T
Abstract: The utilization of the internet on learning is growing rapidly including on physics learning at every level. The aim of this research is to develop the weblogs to facilitate more various and easier learning resources. The weblogs development used 4D methods (define, design, develop and disseminate). The test of the product response was applied on 22 students. The questionnaire covered four aspects which were the language, the subject matter content, the layout, and the usefulness. The response items were measured using the Likert scale from 1 to 4 scales. The analysis technique was descriptive statistics. Results of analysis in the aspect of 3.09, 3.14, 3.21, and 3.28 from scale 4 respectively. Overall the result of student response analysis indicates that this weblog is good (3.18 out of 4) for use in learning. The further research should study on the impact of this media to the learning performance.